The Expression of National Identity in a Cultural Centre - Stanišauskienė, Eglė; Kepalienė, Inga; Žygaitienė, Birutė (Technium Social Sciences Journal, 2026)
In times of globalisation and cultural interaction, the preservation of national identity is particularly important. Cultural centres play a key role in fostering national values, building community, and preserving traditions. The success of preserving national identity depends on community involvement and financial support, and innovation, including digital technologies and youth engagement initiatives. The article examines the role of cultural centres in the formation of national identity, the role of digital technologies in disseminating national identity, and the involvement of young people in strengthening national identity through educational and cultural activities.